Enhancing Prospective Teachers´ Development Through Problem-Based Learning in Chemistry Education - OZDEN, MUSTAFA (Asian Journal of Chemistry, 2010)
The purpose of this study was to compare the attitudes towards chemistry and academic achievement of prospective elementary school teachers in a problem-based curriculum with those in a conventional elementary school teacher training program about ‘solutions and properties’ unit. The results of this study showed that there was a statistically significant difference between the control and experimental groups in terms of students' academic achievement and attitudes towards chemistry. In addition, it was seen that problem based learning model applied in experimental group had more positive effects about conceptual development than control group and students' evaluation of problem based learning showed that students were happy with the problem based learning and enjoyed the problem based learning model.